2010 IEEE Symposium on Visual Analytics Science and Technology 2010
DOI: 10.1109/vast.2010.5652890
|View full text |Cite
|
Sign up to set email alerts
|

Interactive querying of temporal data using a comic strip metaphor

Abstract: Finding patterns in temporal data is an important data analysis task in many domains. Static visualizations can help users easily see certain instances of patterns, but are not specially designed to support systematic analysis tasks, such as finding all instances of a pattern automatically. VizPattern is an interactive visual query environment that uses a comic strip metaphor to enable users to easily and quickly define and locate complex temporal patterns. Evaluations provide evidence that VizPattern is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…al [11,12] have addressed some of those problems by proposing a visual query language that is easily understood and specified by users. However, their comic strip metaphor is not well suited for expressing longer repetitions or parallel (alternate) paths.…”
Section: Query Languages For Event Sequence and Temporal Datamentioning
confidence: 99%
“…al [11,12] have addressed some of those problems by proposing a visual query language that is easily understood and specified by users. However, their comic strip metaphor is not well suited for expressing longer repetitions or parallel (alternate) paths.…”
Section: Query Languages For Event Sequence and Temporal Datamentioning
confidence: 99%
“…We suggest that, while the concept of incorporating narrative visualization techniques, such as comics and storyboards, into applications for visual analysis, is not entirely novel (ap Cenydd et al, 2011;Jin and Szekely, 2010 ;Hossain et al. 2012), it is of growing interest and there is still significant research to be done in understanding how we can work with storytelling approaches in this field.…”
Section: Narrative Visualisation As the Missing Linkmentioning
confidence: 99%
“…Likewise, behavioral experiment systems such as OpenSesame [MST12] or Presentation from Neurobehavioral Systems intend to produce visual stimuli through their particular framework. Heer et al [HB10] identified limitations of Amazon Mechanical Turk as a platform to conduct graphical perception experiments and they recommend to use it only for recruitment and participant management but launch a evaluation/visualization system via Flash (e.g., [HB10]), Java Web Start (e.g., [JS10]), or JavaScript. USEMATE [ASJ10] is a system for administrating and conducting usability experiments.…”
Section: Related Workmentioning
confidence: 99%